Uptake and bioaccumulation of three widely prescribed pharmaceutically active compounds in tomato fruits and mediated effects on fruit quality attributes - Christou, Anastasis; Kyriacou, Marios C.; Georgiadou, Egli C.; Papamarkou, Rafail; Hapeshi, Evroula; Karaolia, Popi; Michael, Costas; Fotopoulos, Vasileios; Fatta-Kassinos, Despo (My University, 2019)
Pharmaceutically active compounds (PhACs) released in agroecosystems have been found to be taken up by and accumulated in the edible parts of crop plants. By employing simulated hydroponic cultivation under controlled conditions, the present study aimed at evaluating 1) the uptake and bioaccumulation of three common PhACs (diclofenac, DCF; sulfamethoxazole, SMX; trimethoprim, TMP), either applied individually (10 μg L-1) or as mixture (10 μg L-1 each), in tomato fruits harvested from the first three fruit sets, and 2) the PhACs-mediated effects on fruit quality attributes. DCF was not detected in tomato fruits, whereas both SMX and TMP were detected in varying concentrations in fruits, depending on the time of harvest, the mode of application and the allocation of plants in the greenhouse. The studied PhACs applied at environmentally relevant concentrations did not significantly affect plant productivity. Nevertheless, important fruit quality attributes, such as soluble solids and carbohydrate (fructose, glucose, sucrose, total sugars) content were significantly impacted by all studied PhACs applied individually, suggesting that for DCF, potentially its transformation products (TPs) (not examined in this study) may exert significant effects on fruits quality attributes. In addition, no additive or synergistic effects of the mixture of PhACs on studied fruits quality attributes were revealed. Gene expression analysis showed that the PhACs-mediated effects on the carbohydrate content of fruits can be attributed, at least to some extent, to the significant modulation of the abundance of transcripts related to the biosynthesis and catabolism of sucrose, such as SlSuSys, SlLin5 and SlLin7. To our knowledge, this is the first report highlighting the potential effects of PhACs released in agroecosystems on the quality of widely consumed agricultural products. In any case, further studies are warranted for the overall assessment of the potential impacts of PhACs on the quality of agricultural products under conventional agricultural conditions.
Keywords: Fruit quality; Gene expression analysis; Pharmaceutically active compounds; Solanum lycopersicum L.; Soluble carbohydrates; Sucrose